Exploration of Frugal Living in Facing the Flexing Phenomenon in the Millennial Generation (Sharia Economic Concept) - Lusiana, Lusiana; Fathimah, Ema; Daulay, Wasti Indah Haryani (MUAMALATUNA, 2023)
This research aims to explain the exploration of Frugal living as an alternative in dealing with the flexing phenomenon in the millennial generation, with a sharia economic approach. The flexing phenomenon, which reflects the behavior of showing off or displaying wealth proudly, has become a trend among millennials, especially on social media. This can lead to overconsumption, financial imbalance, and neglect of ethical financial principles. This research uses qualitative data type, using a phenomenological approach to understand the subjective meaning of various phenomena of the millennial generation who tend to flex. Rendom data collection is from scientific articles, understanding and information from various online media. The data collected will be analyzed from the perspective of Islamic economics, which includes the principles of justice, empowerment, and financial balance. The research shows that it is a meaningful alternative for the millennial generation in dealing with the flexing phenomenon. The application of Islamic economic principles in providing a deeper understanding of economic benefits and the importance of managing finances wisely can also strengthen awareness of balanced economic benefits and have a positive impact on the financial well-being of individuals and society as a whole. It is hoped that this research can serve as a foothold for policy measures in mitigating excessive flexing practices and promoting more ethical and sustainable consumption behavior in the millennial generation